2004
DOI: 10.1159/000076585
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and Urolithiasis

Abstract: Several studies have indicated that up to 60% of idiopathic calcium stone formers present hypercalciuria. Many authors have described reduced bone mineral density (BMD) in stoneformers with hypercalciuria, but osteopenia has also been found in normocalciuric patients. Moreover, Jaeger’s group found that bone mass was reduced in all patients with calcium stone disease, independently of hypercalciuria. Many factors may contribute to the pathogenesis of osteopenia in stone formers. A predominant role has been giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 27 publications
0
48
0
Order By: Relevance
“…Patient 3 was treated initially with IV Zoledronic acid but was subsequently switched to oral alendronate due to one short-lived episode of hypocalcemic tetany. In four patients (1,4,5,7), previous pharmacologic anticalciuric treatment was continued. No adverse effects were recorded during the treatment with alendronate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient 3 was treated initially with IV Zoledronic acid but was subsequently switched to oral alendronate due to one short-lived episode of hypocalcemic tetany. In four patients (1,4,5,7), previous pharmacologic anticalciuric treatment was continued. No adverse effects were recorded during the treatment with alendronate.…”
Section: Resultsmentioning
confidence: 99%
“…In adults, the association of hypercalciuria with osteopenia is well established [4][5][6][7]. In those with severe osteopenia, Jaeger et al [8] found significantly higher incidence of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bone mass and high risk for osteoporotic fractures as a consequence of PTH and vitamin D abnormalities have also been documented in calcium stone formers [12,13,14,15], as well as a contributing role of FGF-23 and KLOTHO gene polymorphism in the pathogenesis of calcium nephrolithiasis [16,17]. Therefore, FGF-23 and KLOTHO are likely to influence the vitamin D status in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of thiazides is not always sufficient, as it has been demonstrated that a high percentage of patients with recurrent renal calcium stones have an osteopenia/osteoporosis [20,21,22] that could benefit from treatment with an anti-reabsorption drug. The bisphosphonates are a group of therapeutic drugs widely used in the treatment of osteoporosis [23], although they are not free of adverse effects, one of the most severe being osteonecrosis of the jaw.…”
Section: Discussionmentioning
confidence: 99%